Pengaruh Kompensasi Nonfinasial Dan Pengalaman Kerja Terhadap Kinerja Pegawai Dinas Perkebunan Prov Sumbar - Yusnaena Herlin Mutia.A (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2015)
This study was conducted to determine the effect of Compensation Nonfinasial And Work Experience Against Employee Performance Plantation Office of West Sumatra Province. With a sample of 61 people. sampling technique using Slovin formula. processing of data by using multiple regression analysis The results of this study illustrate that non-financial compensation variable has no effect on employee performance Plantation Office Province West Sumatra This is because the distribution of non-financial compensation in West Sumatera Plantation Office unevenly distributed to employees, Work experience affect the performance of employees at the Department of West Sumatera Plantations. Non-financial compensation and employee experiences affect together - the same on employee performance Plantation Office of West Sumatra province.Keywords: non-financial compensation, Work Experience and Performance.